Matching in the civil service: A market design approach to public administration and development - Ashutosh Thakur (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Using a matching theory perspective, I analyze the design and the impact of Indian Civil Service state assignment mechanisms used to allocate elite civil servants to different parts of the country. I find that a recent change in the matching mechanism in 2008 has systematically skewed assignments by assigning relatively poor quality bureaucrats to disadvantaged states: regions with external foreign conflict, states with internal political strife, and newly-formed states. This paper i) analyzes the causes of these imbalances, ii) assesses the impact of this mechanism change on state capacity, development outcomes, and bureaucratic performance, and iii) highlights trade-offs in implementing alternate mechanisms. Global balance in quality across state cadres is a unique constraint that arises when applying matching to political economy settings, as the mechanism designer is a paternalistic central planner. Thus, less is left to the market compared to most canonical matching applications. On the other hand, the use of matching in political economy is also novel, and careful understanding of how different matching mechanisms address underlying correlations in the data has far-reaching consequences for bureaucratic performance and development outcomes.
Keywords: D73; C78; O1; 330; matching; civil service; bureaucracy; quality balance constraint; revenue collection